The clash of civilizations thesis and Muslims: the search for an alternative paradigm - Abdullah, al-Ahsan (Islamic Research Institute (IRI), 2009)
The clash of civilizations thesis, first formulated by Bernard Lewis and popularized by Samuel Huntington in the 1990s was, in the course of time, embraced by President George W. Bush for execution, virtually making it the cornerstone of US foreign policy during the early years of the 21st century. The situation thus created has pushed the Muslim world to the centre-stage of international politics. An in-depth analysis, however, finds the thesis to be seriously flawed. Despite differences, Islamic and Western transparency and freedom of choice. The idea of a clash between these two civilizations appears to be based on misapprehension of certain events in history and its implications for world peace are simply horrendous. Luckily there are indications that the new American administration under President Obama seems to have realized the essential flaw of the clash civilizations thesis. The present article ventures to explore the outlines of an alternative paradigm that might pave the ground for peaceful civilizational co-existence.